La Vulva - Arauz, Carlos (Revista Universidad de Guayaquil, 1998)
The most extraordinary installation suggestive intelligence toward mystery monologue of happiness universal private dream tunnel in infinite time with the exalted functional bliss incredible matrix with explosive charge decálogo and synthesis of wonder motive of naïve and pure pressure checkmate to the chessboard of love all efforts lead to the center of all things beautifully shaped that women refine in accordance with horizontal conduct knowledge and willingness in the exercise of human goods in transit through eternity frame of astonishing simplicity as life and death are evidence.